2021
DOI: 10.32615/ps.2021.048
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic traits and biochemical responses in strawberry (Fragaria × ananassa Duch.) leaves supplemented with LED lights

Abstract: Abbreviations: B − blue light supplementation; Car − carotenoids; Chl − chlorophyll; Ci − intercellular CO2 concentration; DEPS − de-epoxidation state of xanthophyll cycle pigments; ETR − electron transport rate; flav − flavonoids; FM − fresh mass; Fv/Fm − maximum quantum yield of PSII; G − green light supplementation; gm − mesophyll conductance; gs − stomatal conductance; J1300 − electron transport obtained at saturating light; LED − light emitting diode; NBI − nitrogen balance index; NS − control; PN -net ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Plant gas exchange parameters have been used as a reliable indicator for strawberry production (Choi et al, 2015;Lauria et al, 2021). Obtained results revealed that, LM6 has the best effect on net photosynthetic rate (A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant gas exchange parameters have been used as a reliable indicator for strawberry production (Choi et al, 2015;Lauria et al, 2021). Obtained results revealed that, LM6 has the best effect on net photosynthetic rate (A).…”
Section: Discussionmentioning
confidence: 99%
“…Blue light improved leaflet length (Choi et al, 2015), plant height, leaf number and area (Uddin et al, 2018), and strawberry fruit yield (Choi et al, 2015;Uddin et al, 2018). Red and blue lights enhanced the stress resistance levels in strawberry plants (Lauria et al, 2021). There are no data for the combination of light intensity, light quality, and photoperiod with orthogonal design known to date.…”
Section: Introductionmentioning
confidence: 98%
“…The average of growing conditions were: 25.9 °C mean temperature, 52 % humidity and 434 μmol m -2 s -1 daily mean solar light radiation. All plants were fed with a nutrient solution optimized in a previous study for strawberry fruit growth (Lauria et al, 2021) with minor modifications and containing N-NO3 − 10.0 mM, N-NH4 + 1.0 mM, P-PO4 3-1.0 mM, K + 6.5 mM, Ca 2+ 5.2 mM, Mg 2+ 1.2 mM, S-SO4 2-4.2 mM, Fe 2+ 20.0 μM, BO 3-30.0 μM, Cu 2+ 1.0 μM, Zn 2+ 5.0 μM, Mn 2+ 10.0 μM, Mo 3+ 1.0 μM; EC and pH were 2.25 dS m -1 and 5.6, respectively. These latter parameters were checked daily and adjusted to keep them within 10 % of the values measured in the fresh nutrient solution.…”
Section: Plant Material Growing Conditions and Fruit Yield Measurementmentioning
confidence: 99%
“…Light is one of the most important environmental factors for plant growth, development, and fruit quality. The utilization of appropriate lighting parameters (i.e., intensity, photoperiod, and spectral quality) can regulate and enhance plant and fruit cell function, appearance and production of metabolites in food crops, especially in indoor cultivations (Lauria et al, 2021). Nowadays, light emitting diodes (LEDs) have gained popularity due to their energy-saving, cheaper and compact nature than traditional light sources (i.e., fluorescent, filament and high-pressure sodium lamps; Al Murad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%